GAYA KEPEMIMPINAN DAN KINERJA KARYAWAN: TINJAUAN LITERATUR - Antaiwan Bowo Pranogyo; Junaidi Hendro (J-MIND (Jurnal Manajemen Indonesia), 2022)
This article focuses on the relationship between leadership style and overall employee performance. Research on the relationship between leadership styles and employee performance continues to yield mixed results. The goal of this study was to determine the relationship between management style and overall employee performance by comparing the results of primary studies to these variables. The method employed is a conceptual analysis of numerous previous studies conducted over the last ten years. The findings confirmed that there is a widespread and fine correlation between leadership style and worker performance, particularly in the Indonesian context, where social members of the family are a concern in society. This implies that the leader must be capable of creating a favorable management style in order to inspire improved employee performance, despite the fact that this isn't the most important factor to consider.